CAREER MANAGEMENT IN MANUFACTURING SECTOR WITH REFERENCE TO SELECT INDUSTRIES IN MYSORE DISTRICT- KARNATAKA - Hasan, Kashif; Johri, Sanjay Mohan; Naik, Manjushree G; Kazmi, Syed Sajid Husain; Saxena, Sagar (International Journal of Psychosocial Rehabilitation, 2020)
The use of media in promoting mental health is relatively a new phenomenon and indeed a complex idea of study in the frequently changing scenario of technological arena. Media has tremendous ability to impact the human minds. It not only influences the people to purchase and use products but also captivates the minds and impacts the cognition. The negative messages and images delivered by media will promote negative assertiveness and the subsequent coverage by media nourishes the already existing negative perception of public and mental health. Hence there is a need to disseminate proper information.Media can be used to bring in changes in the society. The potentialities hidden in the media can be used to create and impart knowledge, develop favourable behaviours and attitudes and to change the blatant behaviours in the society. Media should be utilised in such a way that the only positive aspects of media should be designed and adopted to be the harbingers of the changes in the society. The negative sides of media should be ignored. The media should be used and can reduce the stigma thatched to the mental illness as it is capable of worsening the stigma attached to the mental disorder. It should be acknowledged by all forms of media platforms including the social media and mainstream media adhere to the ethical values of reframing from broadcasting, printing and uploading fake information into the public domain. Mental health professionals play a crucial role in creating awareness among public and educating them over the illness and its present condition.